SUSTAINABILITY ACCONTING (AKUNTANSI KEBERLANJUTAN) - Cahyanti, Lisa Suci (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
Abstract: The description provides a brief description of the emergence of thinking abaut accounting for subtainability and related issues. Staring with a brief summary of the abstraction, followed by a discussion of limitations of the current accounting system in considering the impact of non-monetery, and brief comment abaut the debate over the divination of substainability (required in order to develop quidelines for the implementation in practice). The next section, a review of literature on non-market valuation, such assesments ecological footprints, triple bottom line reporting and trends in environmental accounting. End with, does all this discussion mean for the accounting and corporate management and a brief description about the future of subtainability reporting model and the possibilities for busness development.Keywords: accounting, subtainability